What Persecution To Endure, To Resist, or To Flee? - Petri, Dennis P. (Evangelical review of theology, 2022)
How to respond to persecution is a complex decision involving both principled and strategic considerations. In this article, two of the world's leading experts on religious persecution draw on both Scripture and their considerable experience to discuss the options comprehensively.